Design and 3D-model of a dynamic bubble trap for cardiopulmonary bypass - A. P. Kuleshov; A. S. Buchnev; A. A. Drobyshev; G. P. Itkin (Вестник трансплантологии и искусственных органов)
The use of extracorporeal circulation systems (cardiopulmonary bypass pumps, ECMO) can lead to brain and coronary artery microembolism, which significantly reduces postoperative rehabilitation and often leads to severe complications. Microembolism occurs when oxygen or air microbubbles (MBs) enter the arterial system of patients. Existing CPB pumps come with built-in bubble trap systems but cannot remove bubbles in the circuit. ECMO devices have arterial filters but cannot reliably filter out <40 μm bubbles in a wide flow range. We have proposed an alternative method that involves the use of an efficient dynamic bubble trap (DBT) for both large and small bubbles. The design includes development of two DBT variants for hemodynamic conditions of adult and pediatric patients. The device is installed in the CPB pump and ECMO outlet lines. It provides sufficient bubble separation from the lines in a blood flow of 3.0–5.0 L/min for adults and 0.5–2.0 L/min for children. The developed computer models have shown that MBs smaller than 10 μm can be filtered. The use of this device will greatly reduce the likelihood of air embolism and provide the opportunity to reconsider the concept of expensive arterial filters.